2003
DOI: 10.1196/annals.1304.004
|View full text |Cite
|
Sign up to set email alerts
|

Agmatine: At the Crossroads of the Arginine Pathways

Abstract: In acute inflammatory responses, such as wound healing and glomerulonephritis, arginine is the precursor for production of the cytostatic molecule nitric oxide (NO) and the pro-proliferative polyamines. NO is an early phase response whereas increased generation of polyamines is requisite for the later, repair phase response. The temporal switch of arginine as a substrate for the inducible nitric oxide synthase (iNOS)/NO axis to arginase/ornithine decarboxylase (ODC)/polyamine axis is subject to regulation by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 85 publications
(156 reference statements)
1
33
0
2
Order By: Relevance
“…[14][15][16][17][18][19] The role of L-Arg in the immune system has been suggested by the markedly diminished T-cell responses found in patients with trauma, liver transplantation, and some tumors where L-Arg is reduced by the excess production of arginase 1 in myeloid-derived suppressor cells (MDSCs). 2,3 Both in vitro and animal models have shown that the lack of L-Arg not only blocks T-cell proliferation, but also induces molecular changes including a low expression of CD3 chain and a decreased production of cytokines such IFN␥, but not IL-2.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19] The role of L-Arg in the immune system has been suggested by the markedly diminished T-cell responses found in patients with trauma, liver transplantation, and some tumors where L-Arg is reduced by the excess production of arginase 1 in myeloid-derived suppressor cells (MDSCs). 2,3 Both in vitro and animal models have shown that the lack of L-Arg not only blocks T-cell proliferation, but also induces molecular changes including a low expression of CD3 chain and a decreased production of cytokines such IFN␥, but not IL-2.…”
Section: Discussionmentioning
confidence: 99%
“…Agmatine is an intermediate in the arginine decarboxylase (ADC) pathway for arginine degradation (180). In P. aeruginosa PAO1, the TFR AguR controls expression of the aguAB operon, involved in agmatine utilization, and is induced by agmatine YijC-O157 SG2156 AB_4089 EFER_3797 ECL_05025 ROD_37821 Kvar_4969 KP1_0117 SBG_3617 STY3747 ESA_03803 PANA_3837 Dd703_3786 Rahaq_4293 plu4738 HDEF_0375 VF_2438 VC0152 PM1345 HI0570 D11S_0300 APL_1480 SO_0198 MAB_1589 0017_02262 0016_02765 SAV2759 SSQG_05532 SSEG_08400 SCAB27351 SSDG_03331 SSOG_03491 SGR2032 SCO5483 SSAG_05048 SSBG_03542 MSMEG_1741 MAB_1424c ro01410 SSMG_01660 PSPTO_4908 PSPA7_5613 DesT PFL_0610 nfa12930 PA1539 PSPA7_3792 A1S_2460 0017_01408 0016_00290 Smlt2833 XCC3880 …”
Section: Tfrs and Amino Acid Metabolismmentioning
confidence: 99%
“…Therefore, chlamydiae may encounter an unknown acidic environment prior to endocytosis. Alternatively, this arginine metabolic system could have a function different from pH homeostasis, such as reducing polyamine levels in eukaryotic cells, which inhibits cellular replication and proliferation (38), or inhibiting nitric oxide production.…”
Section: Vol 187 2007mentioning
confidence: 99%